Evaluation of intraocular lens position and retinal shape in negative dysphotopsia using high-resolution magnetic resonance imaging. Issue 8 (August 2021) - van Vught, Luc; Dekker, Cornelis E.; Stoel, Berend C.; Luyten, Gregorius P.M.; Beenakker, Jan-Willem M.
Abstract : High-resolution ocular MRI evaluations of both the IOL position and the retinal shape did not show statistically significant differences between patients with and without negative dysphotopsia. Abstract : Purpose: To assess potential relationships of intraocular lens (IOL) position and retinal shape in negative dysphotopsia (ND). Setting: Department of Ophthalmology, Leiden University Medical Center, Leiden, the Netherlands. Design: Case-control study. Methods: High-resolution ocular magnetic resonance imaging (MRI) scans were performed in patients with ND and pseudophakic controls, and subsequently used to determine the displacement and tilt of the in-the-bag IOL about the pupil and iris. In addition, anterior segment tomography was used to assess the iris–IOL distance. Furthermore, the retinal shape was quantified from the MRI scans by fitting an ellipse to the segmented inner boundary of the retina. Both the IOL position and retinal shape were compared between groups to assess their potential role in the etiology of ND. Results: In total, 37 patients with ND and 26 pseudophakic controls were included in the study. The mean displacement and tilt of the IOL were less than 0.1 mm and 0.5 degrees, respectively, in both groups and all directions. The corresponding mean iris–IOL distance was 1.1 mm in both groups. Neither of these values differed statistically significantly between groups (all P values >.6). The retinal shape showed large variations but was not statistically significantly different between the groups in both the left–right ( P = .10) and the anterior–posterior ( P = .56) directions. Conclusions: In this study, the in-the-bag IOL position and retinal shape did not statistically significantly differ between patients with ND and the general pseudophakic population. Given the large variation in retinal shape between subjects, however, it could still be an important factor in a multifactorial origin of ND.